Determinants for grading Malaysian rice - Che Pa, Noraziah; Yusoff, Nooraini; Ahmad, Nor Hayati (AIP Publishing LLC, 2016)
Due to un-uniformity of rice grading practices in Malaysia, zones which actively producing rice in Malaysia are using their own way of grading rice. Rice grading is important in determining rice quality and its subsequent price in the market. It is an important process applied in the rice production industry with the purpose of ensuring that the rice produced for the market meets the quality requirements of consumer.Two important aspects that need to be considered in determining rice grades are grading technique and determinants to be used for grading (usually referred as rice attributes).This article proposes the list of determinants to be used in grading Malaysian rice. Determinants were explored through combination of extensive literature review and series of interview with the domain experts and practitioners.The proposed determinants are believed to be beneficial to BERNAS in improving the current Malaysian rice grading process.